Glaucoma tube shunt surgery with repeat penetrating keratoplasty in an aphakic patient - Bryce Chiang; Karen Wai; Andrea Naranjo; Stephen Smith; Jennifer Rose-Nussbaumer; Wendy W. Liu (American Journal of Ophthalmology Case Reports)
We present a complicated case of mixed mechanism glaucoma in the setting of failed corneal transplant and aphakia. The patient was a 54-year old male with HLA B27 uveitis and prior open globe injury. He was left aphakic after cataract extraction and had a subsequent corneal transplant for bullous keratopathy. Due to elevated intraocular pressure in the setting of a failed corneal graft, the decision was made to insert a pars plana tube shunt and perform repeat penetrating keratoplasty as a combined case with the glaucoma, cornea, and retina services. We illustrate the surgical steps and decision making and in this complex case.